Demonstrating Potential of Cell Therapy for Wilson's Disease with the Long-Evans Cinnamon Rat Model - Jaber, Fadi Luc (Methods Mol Biol, 2017)
Wilson's disease (WD) is characterized by the inability to excrete copper (Cu) from the body with progressive tissue injury, especially in liver and brain. The molecular defect in WD concerns mutations in ATP7B gene leading to loss of Cu transport from the hepatocyte to the bile canaliculus. While drugs, e.g., Cu chelators, have been available for several decades, these must be taken lifelong, which can be difficult due to issues of compliance or side effects. Many individuals may require liver transplantation, which can also be difficult due to donor organ shortages. Therefore, achieving permanent cures via cell or gene therapy are of great interest for WD. Cell therapy is feasible because transplanted hepatocytes can integrate in liver parenchyma and restore deficient functions, including transport of Cu into bile. The availability of authentic animal models that recapitulate hepatic WD, especially the Long-Evans Cinnamon (LEC) rat, has advanced cell transplantation research in WD. We describe requirements for cell therapy in animal models with several standardized methods for studies to test or refine cell therapy strategies in WD.